2015
DOI: 10.4236/ojrad.2015.52011
|View full text |Cite
|
Sign up to set email alerts
|

MRI Evaluation of Acute Internal Derangement of Knee

Abstract: Introduction: Internal derangement of the knee is a blanket term used to cover a group of disorders involving destruction of the normal functioning of the ligaments or cartilages. MRI provides excellent soft tissue contrast and is capable of evaluating the soft tissue and bony structures in multiple imaging planes which provide significant advantage in IDK. Methods and Materials: A prospective study of hundred twenty patients who underwent MRI for the diagnosis of internal derangement of knee between the perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…In another study conducted by Jamal Yaqoob et al it was observed that among 54 patients, 31(57.4%) had medial meniscal tear, 12(22.2%) had lateral meniscal tear and 11(20.3%) had ACL Tear. 15,16 Hence, further studies with larger sample size are required to agree/ disagree with the results of study and also needs arthroscopic correlation to confirm the MRI findings.…”
Section: Discussionmentioning
confidence: 91%
“…In another study conducted by Jamal Yaqoob et al it was observed that among 54 patients, 31(57.4%) had medial meniscal tear, 12(22.2%) had lateral meniscal tear and 11(20.3%) had ACL Tear. 15,16 Hence, further studies with larger sample size are required to agree/ disagree with the results of study and also needs arthroscopic correlation to confirm the MRI findings.…”
Section: Discussionmentioning
confidence: 91%
“…6,[8][9][10][11] Grade-2 was the commonest meniscal tear in the current study which contrasts with the results, who reported grade-3 as the commonest grade of meniscal tear. 12 Vertical tears were found to be the commonest type of meniscal tear. This contrasts with the previous finding of horizontal tear being the commonest meniscal type also reported.…”
Section: Discussionmentioning
confidence: 99%
“…Similar association was reported previous studies. 12,[16][17] Popliteal cyst was the commonest cystic lesion (10%) involving the knee joint. Similar observations had been reported previously (10%).…”
Section: Discussionmentioning
confidence: 99%
“…Mc Cauley et al [15], Arumugam et al [21] and Spindler et al [14] ACL tear. In the present study, in 3 patients bone bruises were associated with MCL tear.…”
Section: Fibulamentioning
confidence: 99%